Mms19 is a mitotic gene that permits Cdk7 to be fully active as a Cdk-activating kinase - Nag, Rishita Narendra (Development, 2018)
Mms19 encodes a cytosolic iron-sulphur assembly component. We found that Drosophila Mms19 is also essential for mitotic divisions and for the proliferation of diploid cells. Reduced Mms19 activity causes severe mitotic defects in spindle dynamics and chromosome segregation, and loss of zygotic Mms19 prevents the formation of imaginal discs. The lack of mitotic tissue in Mms19(P/P) larvae can be rescued by overexpression of the Cdk-activating kinase (CAK) complex, an activator of mitotic Cdk1, suggesting that Mms19 functions in mitosis to allow CAK (Cdk7/Cyclin H/Mat1) to become fully active as a Cdk1-activating kinase. When bound to Xpd and TFIIH, the CAK subunit Cdk7 phosphorylates transcriptional targets and not cell cycle Cdks. In contrast, free CAK phosphorylates and activates Cdk1. Physical and genetic interaction studies between Mms19 and Xpd suggest that their interaction prevents Xpd from binding to the CAK complex. Xpd bound to Mms19 therefore frees CAK complexes, allowing them to phosphorylate Cdk1 and facilitating progression to metaphase. The structural basis for the competitive interaction with Xpd seems to be the binding of Mms19, core TFIIH and CAK to neighbouring or overlapping regions of Xpd.